Lithuanian industry personnel value orientation towards innovativeness: Analysis, evaluation and improvement possibilities - Maceika, Augustinas; Jančiauskas, Bronius (Business: Theory and Practice, 2010)
The authors of this article established the goal to detect and evaluate the wide possibilities for strengthening the value orientation towards innovativeness in the industrial enterprises. For this purpose exploration of the valuation on the innovativeness as a value was made. The authors of this article performed necessary research, analyses, evaluation and generalization in order to solve this problem. There were methods applied: analysis of information sources, a sociological enquiry of industrial enterprises personnel and correlation analysis. The demand to increase valuation on innovativeness was proved after the investigation. Correlation analysis showed that there is a very weak dependence between evaluated by personnel innovativeness, annual changes and success of activity parameters. Lack of advanced knowledge of management was also established. The way to make a better situation is to use purposeful general politics for innovativeness development in the enterprises, to solve the leadership problems and to equalize the innovativeness level of the separate powerhouses. Article in Lithuanian. Lietuvos pramonės darbuotojų vertybinės orientacijos inovatyvumo atžvilgiu: analizė, vertinimas ir gerinimo galimybės Santrauka. Straipsnio autorių tikslas – išnagrinėti ir įvertinti platesnes galimybes, kurias galima būtų panaudoti pramonės įmonių darbuotojų vertybinių orientacijų inovatyvumui stiprinti. Tuo tikslu buvo ištirtas inovatyvumo kaip vertybės vertinimas pramonės įmonėse. Tam prireikė taikyti tokius metodus: dokumentinės informacijos šaltinių analizę, pramonės įmonių personalo sociologinę apklausą ir koreliacijos analizę. Tyrimo metu nustatytas akivaizdus poreikis vertinti inovatyvumą kaip vertybę. Koreliacijos analizė parodė, kad daugeliu atvejų egzistuoja silpnas ryšys tarp personalo įvertintų inovatyvumo, metinių pokyčių ir veiklos sėkmingumo parametrų. Buvo nustatytas pažangesnės vadybos trūkumas. Situacijai gerinti siūloma taikyti kryptingesnę inovatyvumo ugdymo įmonėse politiką, išspręsti lyderystės problemas ir labiau išlyginti atskirų įtakos grupių inovatyvumo lygį. Reikšminiai žodžiai: inovacijos, inovatyvumas, vertybinės orientacijos, pramonės įmonė, personalo vadyba.